2014
DOI: 10.1002/med.21309
|View full text |Cite
|
Sign up to set email alerts
|

Stem‐Cell Challenges in the Treatment of Alzheimer's Disease: A Long Way from Bench to Bedside

Abstract: Alzheimer's disease (AD) is the most prevalent type of dementia, and its neuropathology is characterized by deposition of insoluble β-amyloid peptides, intracellular neurofibrillary tangles, and the loss of diverse neurons. Current pharmacological treatments for AD relieve symptoms without affecting the major pathological characteristics of the disease. Therefore, it is essential to develop new and effective therapies. Stem-cell types include tissue-specific stem cells, such as neural stem cells and mesenchyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 112 publications
(154 reference statements)
1
44
0
Order By: Relevance
“…Adequate cell types should be selected and integrated in the particulate systems according to the needs of the patients. The use of primary cells, [ 33 ] stem cells [34][35][36] and bioengineered cells [ 37,38 ] are considered a valuable strategy for treatment of several diseases or even for stimulating the regeneration of Figure 1. The chemistry at surface and bulk levels as well as the physical features such as mechanical properties, size, porosity, surface topography/texture, shape and compartmentalization should be carefully considered during the design/engineering of particulate systems for biomedical applications.…”
Section: Reviewmentioning
confidence: 99%
“…Adequate cell types should be selected and integrated in the particulate systems according to the needs of the patients. The use of primary cells, [ 33 ] stem cells [34][35][36] and bioengineered cells [ 37,38 ] are considered a valuable strategy for treatment of several diseases or even for stimulating the regeneration of Figure 1. The chemistry at surface and bulk levels as well as the physical features such as mechanical properties, size, porosity, surface topography/texture, shape and compartmentalization should be carefully considered during the design/engineering of particulate systems for biomedical applications.…”
Section: Reviewmentioning
confidence: 99%
“…However, harvesting BM-MSCs is an invasive procedure, and the yield of viable stem cells is low. These shortcomings limit their usage in clinic [3]. Wharton's Jelly-derived mesenchymal stem cells (WJ-MSCs) have gained much attention since they have a sufficiently high cell yield, without an invasive harvesting procedure and any ethical concern.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some studies reported that the transplanted NSCs overexpressing GDNF or BDNF or NGF improved the locomotive or memory deficits of the animal models with PD, amyotrophic lateral sclerosis, and Alzheimer's disease, probably because of secreted growth factors playing major neurorestorative effects in these studies. 29,[34][35][36] The compositions of the hUCB-MNCs are still not uniform. One study showed that the hUCB-MNCs contain different stem cells and CD34/CD45 is about 60%.…”
Section: Discussionmentioning
confidence: 99%